Modern health concept of non-bovine milk: A review (Indian Journal of Animal Production and Management, 2024)
Milk is considered as the most complete single food available and is a fundamental part of the human diet in which major contribution comes from bovine than that of Non-Bovine Animals (NBA). Among NBAs, goat, camel, and donkey are important components of livestock industry which play vital role in the socio-economic structure in rural areas. The gross composition of the Non-Bovine Milk (NBM) is almost like that of bovine milk, except donkey milk due to its lower fat and protein and higher lactose content. NBM has several health benefits as it is rich source of essential fatty acids, some essential amino acids, micro-nutrients, and several bioactive compounds. Goat and camel milk have smaller fat globules hence known as naturally homogenized milk and have better digestibility and protein utilization. Camel and donkey milk are rich source of vitamin C as compared to bovine milk. Furthermore, the protein composition of NBM is one of the attractive points as compared to bovine milk due to its lower allergenic effects in consumers. NBM is also a very rich source of healthy unsaturated fatty acids. Multiple medicinal and therapeutic anti-allergic, anti-microbial, anti-inflammatory, anti-oxidative and anti-cancerous properties help to promote them as “functional foods” to attract consumers. Goat, camel and donkey milk are well known for their bifidogenic, anti-diabetic and antioxidant effects, respectively. NBM has potential for human well-being though, less awareness, information about the microbiota and its significance for milk quality and safety are challenging fields for further exploration.
Keywords: Milk; Non-Bovine; Goat; Camel; Donkey; Health